2005
DOI: 10.1007/s00210-004-1011-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of somatostatin analogues on chemically induced ischaemia in the rat retina

Abstract: This study investigated the neuroprotective effect of somatostatin, cortistatin and agonists at somatostatin(2) (sst(2)) receptors in retinal explants subjected to chemical ischaemia. Eyecups of female Sprague-Dawley rats (250-300 g) were immersed in PBS buffer or PBS containing iodoacetic acid (IAA; 0.5, 5, 50, 100 mM) and sodium cyanide (NaCN; 2.5, 25, 250, 500 mM) (chemical ischaemia solution) for 15, 30, 45, 60, 120 min (pilot study). Subsequently, eyecups were incubated with (1) PBS, (2) chemical ischaemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
51
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(64 citation statements)
references
References 31 publications
12
51
0
1
Order By: Relevance
“…In studies with an ex vivo model of the rat retina, SRIF analogues have been reported to significantly reduce the ischemic damage suffered by retinal neurons [39]. These observations have been replicated in an ex vivo model of the ischemic mouse retina, where the neuroprotective effects of SRIF have been shown to be mediated by the sst2 receptor.…”
Section: Neuropeptides As Anti-ischemic Agentsmentioning
confidence: 90%
“…In studies with an ex vivo model of the rat retina, SRIF analogues have been reported to significantly reduce the ischemic damage suffered by retinal neurons [39]. These observations have been replicated in an ex vivo model of the ischemic mouse retina, where the neuroprotective effects of SRIF have been shown to be mediated by the sst2 receptor.…”
Section: Neuropeptides As Anti-ischemic Agentsmentioning
confidence: 90%
“…In this model, somatostatin analogs selective for the sst 2 subtype protected the retina from the ischemic insult and were successful in reversing retinal cell death (Mastrodimou et al, 2005). Recent data have shown that the increased presence of sst 2 receptors, in retinas of mice not expressing the sst 1 receptor subtype, protected the retina from ischemia (hypoxia and iodoacetic acid) (Catalani et al, 2007).…”
Section: No/cgmp As Mediators Of the Neuroprotective Effects Of Somatmentioning
confidence: 97%
“…The study by Mastrodimou et al (2005) suggested that rod bipolar and tyrosinehydroxylase sst 2 containing neurons were protected from the ischemic insult, possibly due to the sst 2 involvement in the attenuation of calcium levels. However, the neuroprotection afforded to cholinergic and nNOS containing neurons, that lack sst 2 receptors, could not be explained.…”
Section: No/cgmp As Mediators Of the Neuroprotective Effects Of Somatmentioning
confidence: 99%
“…protects against ischemia-reperfusion injury (Celiker and Ilhan, 2002) and sst 2 agonists attenuate cell death in rat retinal explants subjected to chemical ischemia (Mastrodimou et al, 2005).…”
Section: Retinal Ischemiamentioning
confidence: 99%
“…In particular, in explants of the rat retina subjected in vitro to chemical ischemia, sst 2 agonists prevent, at least in part, the loss of several retinal cell populations, including choline acetyltransferase-, tyrosine hydroxylase-, nitric oxide synthase-positive amacrine cells as well as the rod bipolar cells (Mastrodimou et al, 2005). On the other hand, other studies in a model of in vitro ischemia of the mouse retina have recently demonstrated that the extent of sst 2 -mediated protection may vary among different retinal cell populations , suggesting a high level of complexity within the neuroprotective mechanisms of sst 2 .…”
Section: Page 11 Of 26mentioning
confidence: 99%